Profile of Helen M. Piwnica-Worms - Sarah C. P. Williams (Proceedings of the National Academy of Sciences, 2026)
Helen M. Piwnica-Worms has devoted her career to uncovering how cancer cells evade control and resist treatment. From pioneering work on cell cycle checkpoints to revealing drug resistance mechanisms in breast cancer, her research spans the continuum from basic discovery to clinical translation. A leader in using patient-derived models, she has shown how tumors can adopt reversible, drug-tolerant states and develop resistance. Her recent PNAS Inaugural Article identifies two escape routes in BRCA1 -mutant tumors treated with talazoparib, pointing to new combination therapies. She emphasizes the value of mentorship and persistence in science.